2019
DOI: 10.1038/s42003-019-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Control of biosilica morphology and mechanical performance by the conserved diatom gene Silicanin-1

Abstract: The species-specifically patterned biosilica cell walls of diatoms are paradigms for biological mineral morphogenesis and the evolution of lightweight materials with exceptional mechanical performance. Biosilica formation is a membrane-mediated process that occurs in intracellular compartments, termed silica deposition vesicles (SDVs). Silicanin-1 (Sin1) is a highly conserved protein of the SDV membrane, but its role in biosilica formation has remained elusive. Here we generate Sin1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 35 publications
3
72
0
2
Order By: Relevance
“…[ 175 ] The nanopatterned biosiliceous organic–inorganic hybrid composite is precipitated within the SDVs and ultimately become the frustules (Figure 3C). [ 176 ]…”
Section: Mechanisms Of Microbe‐mediated Mineralizationmentioning
confidence: 99%
“…[ 175 ] The nanopatterned biosiliceous organic–inorganic hybrid composite is precipitated within the SDVs and ultimately become the frustules (Figure 3C). [ 176 ]…”
Section: Mechanisms Of Microbe‐mediated Mineralizationmentioning
confidence: 99%
“…4b). The previous interpretation of missing cross-connection in the sin1 knockout mutants [17], was thus a misinterpretation of a phenotype that exhibits weakly silicified cross-links. This result demonstrated that by applying both skeletonization methods, a more realistic description of the valve phenotypes could be obtained.…”
Section: Discussionmentioning
confidence: 98%
“…While biosilica functionalization using LiDSI is well developed and even enables regioselective incorporation of proteins [30], the genetic engineering of biosilica structure is still in its infancy. Only quite recently, the first genetically induced morphological mutants were generated in diatoms through knockdown and knockout of specific genes [15,17]. One of the mutants (Sin1KO), which was generated by knocking out the sin1 gene in T. pseudonana, exhibited a pleiotropic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Such antibody-labelled genetically modified diatom enables an in vitro selectively cell targeting and selectively killing of neuroblastoma and B-lymphoma cells [113]. Furthermore, the role of gene Silicanin-1 in the control of biosilica morphology has been recently highlighted in Thalassiosira pseudonana, opening new possibilities for future genetic engineering of frustules architectures [114]. A deeper knowledge of biosilicification process as well as the role of organic components of diatom frustules (i.e., proteins silaffins and long-chain polyamines) in biogenesis and formation of nanopatterns in diatom frustules are still a challenge.…”
Section: Biochemistry Molecular Biology and Geneticsmentioning
confidence: 99%